Diseño de un simulador de vuelco de un automóvil compacto para la empresa Cinfovial S.A.S. (2020)
To carry out this project, a diagnosis of the current situation of the dump simulators present in Colombia, Latin America and Europe, respectively, was carried out, in addition to the existing legal regulations, in order to know the operating models and functional characteristics; Then the basic design parameters and functional requirements provided by the company Cinfovial S.A.S were established, including technical and design specifications, among others. Based on the requirements and operating parameters, a conceptual design was proposed, based on the different subsystems that make up the tipping simulator machine, giving way to the evaluation of three alternatives proposed for the simulator's compact car type, of which selected the corresponding one according to the weighting criterion (pugh).